Pengaruh Variasi Injection Speed Dan Holding Pressure Terhadap Sink Mark Pada Produk Tutup Lipstik Dengan Material Polypropylene - Adjie, Grabella Tunngul Kharisma Adjie (KILAT, 2024)
In this research, the effect of variations in injection speed and holding pressure on sink marks that occur in lipstick cap products will be investigated. Determining variations in injection speed and holding pressure is needed so that plastic production results are optimal. Variations in injection speed and holding pressure will be investigated using the full factorial design method with a combination of two independent variables consisting of three levels. Furthermore, proving the effect of these parameters will be carried out by providing several variations of injection speed and holding pressure. After that, the test results will look at the depth of the sink mark and product visuals formed using the quick vision machine. The results show that the injection speed has a significant effect on the sink marks that occur. However, holding pressure also has an effect on changes in sink marks for the better, although not too significant.